An Experiment in Verb Valency Frame Extraction from Croatian Dependency Treebank - Agić, Željko; Šojat, Krešimir; Tadić, Marko (2010)
The paper presents an approach to semi-automatic verb valency frame extraction from the Croatian Dependency Treebank. Our algorithm extracted 1923 verb valency frames for 594 different verbs. We discuss applicability of our method to semi- automatic verb valency lexicon creation and refinement, along with possibilities of utilizing it in the task of parsing Croatian texts.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG